Fiscal Health in Local Government Based on Soft System - Suryawati, Dina; Suryono, Agus; Saleh, Choirul; Muluk, Mujibur Rahman Khairul (JEJAK: Jurnal Ekonomi dan Kebijakan, 2018)
The purpose of this paper is to identify problems and construct a conceptual model related to the local fiscal health condition. The local fiscal health condition is highly dependent on many factors, indicating that local finance is a complex, systemic and unstructured process. The main emphasis in this research is that the researchers attempt to explore the problem situation with the interpretive and naturalistic approach toward the local fiscal health condition and to study, understand, and interpret the meaning of phenomenon. This study uses a soft system methodology (SSM) that is a systemic approach to describe unstructured issues with a structured approach. The successful conceptual model constructed in this research is the survival mechanism of revenues and expenditures model. The results of this study indicate that the main problem of fiscal health condition is from both revenues and expenditures. Revenues problem is indicated by the low local fiscal independence, while expenditures problem is by the high indirect personnel expenditures. The location taken as the unit of analysis was Bondowoso Regency, East Java, Indonesia with the consideration that Bondowoso Regency is one of the four underdeveloped regencies in East Java Province.